Molecular characterization with random amplified microsatellites (RAMs) of Inchi (Caryodendron orinocense K.) - Ana Cruz Morillo Coronado (Revista Colombiana de Biotecnología, 2015)
The Inchi or Cacay (Caryodendron orinocense Karsten) is one of the most promising species of the Amazon and Orinoco Colombian. The main product of Cacay are its almonds, from extracted oil cosmetic, phytotherapeutic and food applications, also has a high content of antioxidants such as Omega 3, 6 and 9 and vitamins like A and E. There are no studies on the molecular characterization of this plant genetic resource; therefore the objective of this research was to characterize the genetic diversity using Random Amplified Microsatellite markers (RAMs). The similarity analysis to 0.50 formed four groups according to geographical location, being materials from Putumayo, Cacayal 19, Pauna and Castilla lowest similarity. Estimated heterozygosity values were 0.16 and 0.28 for the primers CGA and GT, respectively. The percentage of polymorphic loci ranged from 55% for the primer CGA and 90% for the GT. The average Fst value for the 27 materials studied was 0.35, showing the space-temporal dynamics of materials Caryodendron tend toward genetic differentiation, due to their own evolutionary processes and domestication incidence.